Preparasi dan Karakterisasi Mikrokapsul Asam Mefenamat Menggunakan Polimer Natrium Alginat dengan Metode Gelasi Ionik - Sandra Aulia Mardikasari; Suryani Suryani; Marwah Puspitasari (JURNAL ILMU KEFARMASIAN INDONESIA, 2020)
Mefenamic acid belongs to a class of the non-steroidal anti-infl ammatory drugs that work asan analgesic. Mefenamic acid is sensitive to the light and temperature, also has unpleasant odors andtastes. Microencapsulation technology is a technique where the active substance is coated by a thin layerso that the active substance is protected from environmental infl uences. The aim of this research was toformulate and characterize mefenamic acid in the form of microcapsule using ionic gelation methodswith sodium alginate. Preparation was done by comparing the concentrations of sodium alginatepolymers namely, 1%, 2%, and 3%. Success parameters include the entrapment effi ciency, particleshape, particle size distribution, and dissolution. The results on the entrapment effi ciency using UVVISspectrophotometer showed a concentration of 1% polymer has a high value of 94.02%, for particleshapes using the optical microscope showed that three formulas were spherical with the smallest particlesize distribution was 1266 μm. The dissolution test by type II dissolution test showed that the higherthe concentration of polymer used, the slower the drug release. This research provides an alternativeformulation of mefenamic acid microcapsule by using sodium alginate polymer.